Factors Affecting Consideration to Switching from Condominium to Townhome for High Class Market in Bangkok Area During COVID-19 Pandemic - Bavornvit Bangthamai; Pongthon Duangoubpama; Nuttawan Rukkachantarakul; Vongurai, Rawin; Piya Hirunwat (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Purpose: Housing estates such as detached houses, townhouses and townhomes. have become more and more marketable lately, and the popularity of condominiums has declined from COVID-19 pandemic. The keys to success of both townhomes and condominiums in this situation are attracting new consumers and retaining the existing ones. The main purpose of this study is to inspect three categories of antecedents for condominiums consumers’ switching intention: push (i.e. satiation), pull (i.e. perceived value) and mooring (i.e. subjective environmental characteristics) factors using push–pull–mooring (PPM) model. Design/Methodology/Approach: High class townhomes has been selected as the research context. An online survey was proceeded to inspect the proposed research model and hypotheses. The data were collected from 478 respondents living and/or working in Bangkok, who have monthly family income at 150,000 Thai Baht and above by using convenience sampling and snowball sampling method. This study applied the Structural Equation Model (SEM) and Confirmatory Factor Analysis (CFA) to certify the goodness-of-fit of the model and hypothesis testing. Findings: The outcomes revealed that among the push factors satiation with amenity has the highest significant impact on subjective environmental characteristics, followed by satiation with decoration. While among pull factors hedonic value has the highest significant impact on subjective environmental characteristics, followed by perceived privacy and security. As well as subjective environmental characteristics has significantly impact on switching intention. Originality/Value: To contribute a comprehensive understanding of consumers’ switching intention, the researcher used PPM model to construct the research framework. This study enhances the understanding of consumer’s switching intention by locating the push and pull factors based on the differences elements between condominiums and townhomes in correspondence to subjective environmental characteristics.